ICT Integration in Music Education within Ghanaian Colleges of Education: Opportunities, Challenges, and Cultural Realities - Arkhurst, Kow; Obeng, Peter; Yeboah, Richmond Amoh (Indonesian Scientific Publication, 2025)
The integration of information and communication technology is significantly transforming how music is taught and learned and experienced in Ghana. Teacher preparation colleges are central to promoting digital literacy among future educators yet the adoption of ICT in music education remains uneven due to infrastructure limitations and unequal access and cultural influences despite supportive national policies. Teacher preparation colleges are central to promoting digital literacy among future educators. This study examines the effects of ICT integration on music instruction in three Ghanaian Colleges of Education which are Abetifi, Kibi, and Agogo. Using an interpretivist qualitative case study design data were collected through interviews and focus groups and classroom observations. The analysis identified three key themes which is ICT's role in fostering creativity, inclusivity and motivation, persistent challenges such as inadequate devices slow internet and limited training and cultural tensions arising from the intersection of technology and traditional musical practices that exists hence people take different approaches. Although ICT has the potential to revolutionize music education its advantages are not yet equally accessible to all students in these institutions. The digital divide creates barriers that prevents students from achieving their full potential in music learning. Addressing the digital divide through targeted training and context-aware pedagogy and policy support is essential to ensure all students benefit. This is more than important actually. The implementation of ICT tools must be done carefully to prevent further widening of educational inequalities in the digital era and to make sure traditional practices are not completely replaced by modern technology.